Heart transplant survival rate in Iran: a single-center registry report. (June 2014) - Salehi, Mehrdad; Bakhshandeh, Ali Reza; Latifi, Sahar; Rahmanian, Mehrzad
Aim: to determine 1-month and 1-year survival rate in recipients of heart transplants in Imam Khomeini Medical Center. Methods: we analyzed the outcomes of 69 patients who underwent heart transplantation between 2007 and 2010. The 1-month and 1-year survival rates were calculated, and we assessed prognostic factors such as donor and recipient age and sex, graft ischemic time during surgery, and liver and kidney function tests. Results: increased donor age had a significant negative effect on survival rate ( p = 0.005). Sex differences between donor and recipient had no association with transplant outcome and survival rate. The overall 1-month and 1-year survival was 82.6% ( n = 54) and 70% ( n = 48), respectively. Conclusion: heart transplantation is a lifesaving procedure for end-stage heart disorders. Mortality after heart transplantation depends on numerous factors, and thus survival rates differ among centers. The 1-month and 1-year survival rates after heart transplant in our center currently stand at 82.6% and 70%, respectively.